The Constitution’s Peoples: Approaching Community in the Context of Section 35 of the Constitution Act, 1982 - Olthuis, Brent (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractModern negotiations between the Crown (or private parties) and Canada’s Aboriginal peoples are largely based on the legal principles articulated in major court decisions. Yet those decisions have not yet confronted a fundamental question: how, in the first instance, do we determine which groups can lay claim to the Aboriginal and treaty rights “recognized and affirmed” by section 35 of the Constitution Act, 1982?The author argues that this question ought to form the theoretical cornerstone of the doctrine of Aboriginal and treaty rights. It is also of critical significance to the continuing process of reconciliation between the Aboriginal and non-Aboriginal elements of Canadian society. The interlocutors in this process must be identifiable.The community recognition needed to give effect to section 35’s inherently group-centred approach cannot be purely subjective or purely objective in nature. Neither a process of unilateral declaration nor one of pure observation can accurately identify the communities at issue under section 35. Rather, the inquiry requires an exercise of interpretation. To this end, the author proposes guidelines to focus and assist the interpretive process.This analysis ultimately entails a reconsideration of some of the prevailing orthodoxies in Aboriginal law jurisprudence, including the “test” for determining the existence of Aboriginal rights (from R. v. Van der Peet) and the notion that an individual member of a modern, rights-holding, Aboriginal community must prove an ancestral or genealogical link to a member of the group at some earlier time (from R. v. Powley).